Implementation of real time measurement system for precise surveying applications - Setan, Halim; Idris, Khairulnizam M. (2005)

(untitled)
Conventional data gathering is not practical and is subjected to several errors due to human factor or instrumentation limitations, especially the gross and systematic error. Precise surveying (especially deformation monitoring and industrial surveying) requires measurement automation and real time measurement system. To date, several real time measurement systems have been developed for deformation monitoring (DIMONS, Leica GEOMOS, Leica APSWin) and industrial surveying (Leica Axyz). The main aim of this research is to develop and implement a real time measurement system for precise surveying application using high precision Leica TCA2003 robotic total station (RTS). This paper discusses the software/system development methodology and the implementation using Microsoft Visual C++.